Comparison of cellular responses to TGF-β1 and BMP-2 between healthy and torn tendons - Morita, W; Snelling, SJB; Wheway, K; Watkins, B; Appleton, L; Murphy, RJ; Carr, AJ; Dakin, SG (SAGE Publications, 2021)
Background: Tendons heal by fibrotic repair, increasing the likelihood of reinjury. Animal tendon injury and overuse models have identified transforming growth factor beta (TGF-β) and bone morphogenetic proteins (BMPs) as growth factors actively involved in the development of fibrosis, by mediating extracellular matrix synthesis and cell differentiation.